Evaluasi Implementasi Asesmen Kompetensi Minimum (AKM) di MTs Al-Utsmani Kajen Pekalongan dan Dampaknya terhadap Efektivitas Pembelajaran - M. Umar Mahmudi; Moh. Muslih (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
Minimum Competency Assessment (AKM) is measuring truly minimum competencies so that schools and regions can be mapped based on minimum competencies. Minimum competency is the basic competency that students need to be able to learn optimally whatever the material and subject. There are two AKM contents, namely literacy (reading and writing) and numeracy. The method used in this research is descriptive qualitative with literature study data collection techniques. The research results show that (1) Minimum Competency Assessment (AKM) at MTs Al-Utsmani Kajen Pekalongan is carried out in accordance with operational standards, which include planning and preparation, implementation, as well as evaluation, reporting and follow-up and (2) Minimum Competency Assessment (AKM ) at MTs Al-Utsmani Kajen Pekalongan can realize learning effectiveness, which is characterized by efficient use of input; effectiveness of AKM implementation, namely planning, socialization, testing, implementation, monitoring and evaluation, and follow-up; output productivity, namely students can access learning, AKM-based assessments, and other educational services remotely; and the relevance of the outcome, namely that the digital literacy of educators and students is increasingly developing well.